1984
DOI: 10.1007/bf00442448
|View full text |Cite
|
Sign up to set email alerts
|

Lung function in congenital and idiopathic scoliosis

Abstract: The vital capacity (VC) in patients with congenital scoliosis was compared with the VC in idiopathic scoliosis. For any given Cobb angle (a measure of spinal angulation) the loss in VC was approximately 15% greater in congenital scoliosis than in idiopathic scoliosis. The greater impairment of lung function in congenital scoliosis may be due to the associated rib deformity or to an underlying lung anomaly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 8 publications
0
22
0
Order By: Relevance
“…1 Another examined the pulmonary function in children with congenital scoliosis and found that these children had lower vital capacity than children with idiopathic scoliosis. 16 However, no research has been published examining the pulmonary function and quality of life in children treated with early fusion for congenital scoliosis. New treatment options are becoming available to treat congenital scoliosis, such as growing rods and distraction thoracoplasty.…”
mentioning
confidence: 99%
“…1 Another examined the pulmonary function in children with congenital scoliosis and found that these children had lower vital capacity than children with idiopathic scoliosis. 16 However, no research has been published examining the pulmonary function and quality of life in children treated with early fusion for congenital scoliosis. New treatment options are becoming available to treat congenital scoliosis, such as growing rods and distraction thoracoplasty.…”
mentioning
confidence: 99%
“…With these limitations in mind, the data are consistent with previously published reports correlating structure and respiratory function in children with EOS. In a previous report of 24 children with congenital scoliosis studied preoperatively, their vital capacity values (ranging from 13% to 68% of predicted normal values) and their Cobb angles (range, 278-1508) correlated poorly with an r value of 0.5 [9]. More recently, Mayer and Redding reported a poor correlation between the preoperative vital capacities and the Cobb angles of 53 children 5 to 15 years of age with EOS identified from seven collaborating spine centers (r = 0.11) [4] (Fig.…”
Section: Discussionmentioning
confidence: 76%
“…13 Progressive infantile or congenital scoliosis, which develops in early childhood and deforms the rib cage have been shown to result in an increasing impairment of lung function. [3][4][5] It is, therefore, likely that a similar impairment will occur in patients with a congenital kyphosis or kyphoscoliosis developing at an early age. However, a spinal curvature with an associated rib cage deformity developing in adolescence, after the lungs are fully developed, will not have a significant effect on lung function unless there is an extreme deformity or an associated neuromuscular condition causing respiratory muscle paralysis.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] To the best of our knowledge, there has been no large series in the English language of the effect of a congenital kyphosis or kyphoscoliosis on lung function.…”
mentioning
confidence: 99%